Implementasi Merdeka Belajar Bagi Konselor - Kusumawati, Eny; Astuti, Anita Dewi (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2022)
Merdeka Belajar (Freedom to learn) is an idea launched by Nadiem Makarim, the Minister of Education and Culture, to produce superior human resources with character education. Merdeka Belajar is expected to be able to create individuals who are critical, creative, collaborative, and skilled. The purpose of this study is to provide an overview of the implementation of the principle of Merdeka Belajar for prospective counselors to increase their scientific repertoire of prospective counselors. This study uses a descriptive approach by using literature study by processing and collecting research materials in the form of library information that can be obtained from books or journals. The stages are as follows: 1) plan the topic to be studied; 2) Searching for library sources that are relevant to the study and select materials from various appropriate library sources; 3) The information obtained from the study material is then used as a reference in conducting discussions and conclusions. The study results indicate that it is important for counselors and prospective counselors to apply the right learning model to the principles of independent learning. It is hoped that counselors and prospective counselors can answer the challenges in the future.